2004
DOI: 10.1002/j.0022-0337.2004.68.11.tb03862.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Combating Dental Anxiety

Abstract: Dental anxiety and subsequent avoidance of dental care and deterioration of oral health pose a significant problem for the dental profession. In an attempt to elucidate preferences of anxious dental patients, we gathered survey data from 121 persons at a small, private liberal arts college in the mid-Atlantic region of the United States. Half of the respondents experienced dental anxiety, and most of these (66 percent) attributed anxiety to fear of anticipated pain. The majority of anxious patients preferred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 16 publications
2
38
0
2
Order By: Relevance
“…Furthermore, with respect to different specialties within dentistry, participants expressed a preference for male dentists regard-less of their own gender, except for pediatric dentists, a finding that is also consistent with previous studies. 13,18,19 This could be attributed to the female practitioners having greater empathy traits, such as more humanness, compassion, communication through nonverbal cues, caring, patience and an expressive attitude towards patients. 17,20 The preference for a male dentist might be due to various factors, such as the sense of more competency in male compared with female practitioners or the general notion of male dentists as more career-oriented and professional than their female counterparts.…”
Section: Jcdpmentioning
confidence: 99%
“…Furthermore, with respect to different specialties within dentistry, participants expressed a preference for male dentists regard-less of their own gender, except for pediatric dentists, a finding that is also consistent with previous studies. 13,18,19 This could be attributed to the female practitioners having greater empathy traits, such as more humanness, compassion, communication through nonverbal cues, caring, patience and an expressive attitude towards patients. 17,20 The preference for a male dentist might be due to various factors, such as the sense of more competency in male compared with female practitioners or the general notion of male dentists as more career-oriented and professional than their female counterparts.…”
Section: Jcdpmentioning
confidence: 99%
“…They said that liberal arts graduates were more interested in the practice of psychiatry than their classmates from comprehensive universities because psychiatrists must understand the biological, psychological, and social components of illness, they treat the "whole person" assisting in the adaptation of individuals coping with stress, crises, and other problems (Stratton, Elam, & McGrath, 2003, p. 61). Since the majority of patients likely prefer a dentist to be friendly and talkative (Bare & Dundes, 2004, p. 1174, communication skills is one of the key elements. With regard to the above, it can be concluded that in the United States, liberal arts and general education, unlike in Japan, have a clear vision what attributes students need and what training they should take to achieve them during school years.…”
Section: Case Of the Us Toward Liberal Arts Coursementioning
confidence: 99%
“…4 There are multifactorial aetiology of dental anxiety occurrence such as watching dental instruments, surrounding noise the two most anxiety arousing being the injection and the drill sound. 5 Typically dental anxiety is accompanied by physiological and psychological responses such as increased heart rate, increase blood pressure, altered respiration rate, sweating, trembling, feelings of coming danger and tension. The dentist's attitude and manner and the dental environment also play a vital part in dental anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, there is an important notion that has emerged from the past and has also received tremendous importance in present in different domains of medicine is music. 5,6 Dental anxiety is manageable. For the dental practitioner, it is important to know that dental apprehension is a continuum ranging from mild to more severe form rather than a yes and no process.…”
Section: Introductionmentioning
confidence: 99%